A Selective sweep in the Chloroplast DNA of Dioecious Silene (Section Elisanthe) - Muir, Graham; Filatov, Dmitry (Genetics, 2007)
Gene flow occurs predominantly via pollen in angiosperms, leading to stronger population subdivision for maternally inherited markers, relative to paternally or biparentally inherited genes. In contrast to this trend, population subdivision within Silene latifolia and S. dioica, as well as subdivision between the two species, is substantially lower in maternally inherited chloroplast genes compared to paternally inherited Y-linked genes. A significant frequency spectrum bias toward rare polymorphisms and a significant loss of polymorphism in chloroplast genes compared to Y-linked and autosomal genes suggest that intra- and inter-specific subdivision in the chloroplast DNA may have been eroded by a selective sweep that has crossed the S. latifolia and S. dioica species boundary.